تنفيذ الخطاب العربي لترقية مهارة الكلام لدى الطلاب بمعهد النجاح شندي آلوس - Ansari, Muhammad Hafiz; Yuspa, Anida (FASAHAH, 2024)
ABSTRACTThe problem with Pondok An Najah Cindai Alus for Boys students' language activities is that students use Arabic poorly. Speech activities at the boarding school can help and improve the quality of students in using Arabic.This research is descriptive in nature and was conducted using qualitative methods. Researchers assess that speech activities play an important role in improving students' Arabic speaking skills. The data collected was collected using triangulation. The results show that the management of the process of implementing speech activities has not supported the improvement of students' Arabic speaking skills. The results showed that although the implementation of speech activities improved students' Arabic speaking skills, it showed several shortcomings and difficulties experienced by students. Planning a speech at Pondok Modern An-Najah Cindai Alus Putra consists of several stages. They are as follows: 1. Divide groups of speech participants; 2. Determine the speech schedule; 3. Choose a speech theme; 4. Opening and closing of the speech; and 5. OSPM management activities during the speech. In its implementation, there are several stages.This research also proposes that future researchers concentrate on speech activities in various skills, such as istima', qira'ah, and kitabah.Keyword: Public Speaking; Arabic; Speaking Skills. مستخلص البحثالمشكلة في الأنشطة اللغوية لطلاب بمعهد النجاح شندي آلوس هي أن الطلاب يستخدمون اللغة العربية بشكل سيئ. يمكن لأنشطة التخاطب في المعهد أن تساعد وتحسن جودة الطلاب في استخدام اللغة العربية. هذا البحث وصفي بطبيعته وتم إجراؤه باستخدام أساليب نوعية. يقيم الباحث أن أنشطة الكلام تلعب دورا مهما في تحسين مهارة الكلام باللغة العربية لدى الطلاب. تم جمع البيانات التي تم جمعها باستخدام التثليث. أظهرت النتائج أن إدارة عملية تنفيذ أنشطة الكلام لم تدعم تحسين مهارة الكلام باللغة العربية لدى الطلاب. وأظهرت النتائج أنه على الرغم من أن تنفيذ أنشطة الخطابة أدى إلى تحسين مهارة الكلام باللغة العربية لدى الطلاب، إلا أنه أظهر العديد من أوجه القصور والصعوبات التي يعاني منها الطلاب. هناك عدة مراحل في التخطيط لإلقاء خطاب في معهد النجاح  شندي آلوس للبنين على النحو التالي:1).  تقسيم مجموعة الخطابة 2). جدول الخطابة 3). تحديد موضوع الخطابة 4). الافتتاحية والختامية أنشطة الخطابة  5). أنشطة مسؤولي مجلس الطلبة  أثناء أنشطة الخطابة.  بذلك الإضافة ، تقترح هذه الدراسة أن يركز الباحث المستقبل على أنشطة الخطابة في مهارات مختلفة مثل ، الاستماع والقراءة والكتابة.كلمات أساسية : الخطاب; اللغة العربية; مهارة الكلام